Using a teacher support group to develop teacher knowledge of Mandarin teaching via web conferencing technology. Issue 1 (2nd January 2016) - Tseng, Jun-Jie; Lien, Yu-Jen; Chen, Hao-Jan
Abstract : Due to its continuous advancement, web conferencing technology is increasingly being integrated into foreign language education; thus, teachers are able to carve out a niche by providing learners with an opportunity to learn a foreign language at a distance without time and space constraints. However, little is known about the relationship between foreign language teachers' use of web conferencing technology and their technological pedagogical content knowledge (TPACK). This study therefore aims to assist Mandarin as a foreign language (MFL) teachers to develop their TPACK of web conferencing teaching, and a teacher support group is used to facilitate the TPACK development of four MFL teachers. The data related to assessing their TPACK development are derived from an online meeting, reflective reports, and individual interviews. The results indicate that the teachers' TPACK grew due to increased awareness of the affordances and constraints of web conferencing technology in an MFL teaching environment. They understood how to enhance learners' input, expand their interaction, and facilitate their production via the use of Internet resources such as multimedia and web-based applications. The teachers also acknowledged that the teacher support group had played an instrumental role in developing their TPACK of teaching MFL via web conferencing technology. The implications and limitations of the study are also presented.